Association of smoking, p53 and Ki-67 immunomarkers with bladder neoplasms in tribal region of India - Vaishnav, Mitsu; Garg, Sameep; Adhaduk, Brinda (International Journal of Health Sciences, 2022)
Objectives: Going back to the basics of urinary bladder neoplasms and correlation of histopathological diagnosis with age, sex, clinical features, smoking in tribal population of India in today’s day and age. Along with that we are also determining the role of p53 and Ki67 immunomarkers in grading and staging of Urinary Bladder Neoplasms and their correlation with history of smoking. Materials and Methods: This retrospective study was done in a tertiary care hospital affiliated with medical college in tribal region of India. Total 72 cases of transurethral resection of bladder tumors and bladder biopsies were studied over a period of 2 years. The histopathological grading and staging was done according to the WHO/ISUP 2016 classification. The histopathological diagnosis was further correlated with age, sex, clinical features, and history of active smoking. Along with that immunomarkers p53 and Ki-67 were done and correlated with grading and staging of tumors and with history of smoking. The cut-off used was more than 20% positivity for high expression and < 20% for low expression. For descriptive, data median (Interquartile Range) and ratio were used. For categorical variables percentage (%), Fisher exact test and Chi-square test were used. Results were evaluated with SPSS software program. P < 0.05 was considered statistically significant. Results: Out of 72 cases studied, 66 cases were neoplastic. Out of them, bladder neoplasms were common in age group of 41–60 years and there was a male preponderance. Most common clinical feature was hematuria. Smoking was not a risk factor for the development of bladder neoplasms but bladder neoplasms in smokers were associated with higher grading and staging. The most common neoplasm was High Grade Papillary Carcinoma (43.05%). Stage T1 and Stage T2 were seen in 3.03% and 27.8% of cases. P53 and Ki-67 immunomarkers showed higher expression in tumors of higher grade and stage. Conclusion: The take away from this study is bladder neoplasms that are quite versatile and histopathology is the gold standard to confirm these. However, p53and ki-67 gives important information regarding prognosis of tumors and helps in stratification of patients in high risk and low risk groups. Development of bladder carcinoma was independent of history of smoking; however, smoking is associated with higher grading and staging of bladder neoplasms and is also associated with higher expression of p53 and Ki-67 immunomarkers.